Gender Differences in Physical Activity Levels among Male and Female Students in Extracurricular Sports Activities at Katolik St. Gabriel Senior High School, Maumere - Bati, Arnoldus Rivaldy; Saputro, Yulianto Dwi; Artanty, Ary (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2024)
The level of physical activity among adolescents in schools is a key indicator of physical health and socio-emotional development. However, participation and intensity of physical activity often differ significantly between male and female students. This study aims to determine the level of physical activity among male and female students participating in extracurricular sports activities, and to analyze the differences between the two groups. A quantitative comparative approach was employed, involving 60 high school students (30 males and 30 females) who actively participated in sports extracurricular programs. Data were collected using a modified IPAQ-based questionnaire, field observations, and semi-structured interviews. The results showed that male students had a higher physical activity score (mean = 82.4) compared to female students (mean = 64.7), with the t-test indicating a statistically significant difference (p < 0.05). These findings suggest that social, motivational, and cultural factors influence physical participation, particularly by gender. Therefore, extracurricular sports programs should be designed to be more inclusive in order to enhance the engagement of female students.